ASSESSMENT OF OBJECTS AND ATTRACTIONS IN THE KRUENG GEUNIE LHOK KEUTAPANG AREA, PIDIE ACEH REGENCY FOR NATURE TOURISM - Diah Ramadhani; Rahmawaty Rahmawaty; Ternala Alexander Barus (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
Objects and tourist attractions are one of the important elements in the world of tourism. Where objects and tourist attractions can succeed the government's program in preserving the nation's customs and culture as assets that can be sold to tourists and can improve welfare and community participation in preserving the development of a tourist area. The purpose of this study was to determine the potential value of natural tourist attractions. The data collection method was carried out using qualitative methods by conducting in-depth structured interviews, literature studies, field observations and Focus Group Discussions (FGD). Data analysis of the potential objects and natural tourist attractions (ODTWA) is described descriptively and processed using the guidelines for the Analysis of Operation Areas for Natural Tourism Objects and Attractions (ADO-ODTWA). The results showed the ODTWA analysis in the Krueng Geunie area for each criterion of attractiveness 83.33% (adequate), accessibility 91.66% (adequate), socio-economic environmental conditions 58.33% (not feasible), accommodation 66.66% (adequate), 80% (adequate) supporting facilities and infrastructure, and 80% (adequate) clean water availability. Therefore, based on the results of research the Krueng Geunie area deserves to be developed as a natural tourist attraction area.